PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA, TERHADAP KEPUASAN KERJA MELALUI MOTIVASI KERJA SEBAGAI VARIABLE MEDIASI - Wibowo, Ikhsan Rahman; Syarif Ali; Supriadi, Yudi Nur; Renny Husniati (Jurnal Ekonomi STIEP, 2023)
This research is a quantitative research that aims to determine the Effect of Compensation, and Work Environment, on Job Satisfaction Through Work Motivation as a Mediation Variable. This study used 37 employees in the HR and Organizational Division of the Head Office of the Public Company Bulog Jakarta. The data analysis technique used is PLS-based SEM. The results showed (1) compensation has a positive and significant effect on job satisfaction, (2) work environment has a positive and significant effect on job satisfaction, (3) compensation has a positive and significant effect on job satisfaction mediated by work motivation, (4) work environment has a positive and significant effect on job satisfaction mediated by work motivation, (5) work motivation has a positive and significant effect on job satisfaction..